Relationship Between Human Capital and Technological Innovation Growth of Regional Economy and Psychology of New Entrepreneurs in Northeast China - Yu, Xingyang; Liu, Mingji (Frontiers in Psychology, 2021)
The economic restructuring and rapid rise of the economy in Northeast China have resulted in a proliferation of new ventures. Studying the psychology of new entrepreneurs is conducive to understanding the relationship between human capital and economic growth. The work reported here aims to explore the impact of human capital on economic growth in Northeast China and the influencing factors of psychological capital of new entrepreneurs in the entrepreneurial process. Based on Cobb-Douglas production function, the relationship between labor, physical capital, or human capital, and economic growth in Northeast China is analyzed by econometric methods, and a model of human capital and economic growth in Northeast China is constructed. Besides, a psychological capital intervention (PCI) model is proposed to develop the psychological capital of new entrepreneurs, and the psychological quality structure model of entrepreneurial entrepreneurs and its operation mechanism. The results of the empirical analysis demonstrate that the elasticity coefficient of human capital in Northeast China is 0.159,02, five times smaller than that of labor and physical capital. Moreover, 70% of new ventures are willing to accept higher education. The fitting degree of using the PCI model to develop the psychological capital of new ventures is only 0.3%. In addition, the modified external environment psychological capital intervention instead of external environment psychological capital intervention model has a huge operating potential in the macro entrepreneurial environment. In conclusion, the impact of human capital on economic growth in the Northeast is smaller than the impact of labor and material capital investment on regional economic growth. The development of human capital and research on the composition and mechanism of psychological quality of entrepreneurial entrepreneurs is of significant theoretical and practical value to promoting economic growth in the Northeast.